Taritib ago igma its significance in resolving rido (feuds) among Maranao families - Abbas, Jabber M (2008)
This study assesses the significance of Taritib Ago Igma (customary law of Maranao) in resolving rido (feuds or conflicts) among Maranao. Specifically, it sought to find out the following: (1) what is Taritib ago igma, its nature, etymology and history; (2) how does Taritib ago Igma operate in resolving rido (feuds) among Maranao; (3) what are the factors in the proliferation of rido; (4) and what is the context in the interplay of Taritib ago Igma and Islamic Law in resolving rido among the Maranao.